Time, Self, and Intertemporal Choice - Retz Lucci, Cintia (Frontiers in Neuroscience, 2013)
Neuroscientific studies of intertemporal choice (IC) have focused mainly on the neural representation of self-control mechanisms and valuation. This reflects what has been considered as the core of the IC phenomenon. The claim of this paper is that deviations from exponential reward discounting as a function of time might be fully accounted for by the deviation of subjective time from calendar time. This claim is based on evidence that specificities of time perception can modulate discounting. Consequently, time perception is fundamental to IC and it is crucial to understand the mechanisms underlying time processing in different situations; to investigate when human time perception differs from time as represented by the calendar metric system; and to study how time perception predicts choices. This paper surveys the recent literature on time perception in order to discuss the measuring of IC through time-perception specificities. The notion of self is also discussed within this temporal perspective. If time perception modulates discounting, and time perception is related to self, the relationship between self and time perception becomes a new path to be explored in the IC studies.